Heredamiento – umowa dziedziczenia czy hybryda umowy prawa spadkowego i rodzinnego - Lubaś, Natalia (Problemy Prawa Prywatnego Międzynarodowego, 2022)
This article addresses the issues related to heredamiento - an agreement as to succession, characteristic of the Catalan legal system (Spain), the centuries-long functioning of which may be an inspiration for other legislators. The paper first attempts to locate this institution in the context of history and terminology. Further, it explains and describes the functioning of heredamiento in the provisions of Catalan law currently in force. The article then discusses the centuries-old location of this institution at the junction of succession law and family law. The paper also presents issues relating to the conflict of laws rules of private international law and the conflict of law rules of interregional law that are characteristic of the Spanish legal system. Therefore, introducing the reader to the institution of heredamiento, the author suggests that the Polish legislator should not cease looking for legal instruments adjusted and adapted to social realities, which would adequately protect the interests of both future decedents and heirs.